Participatory Budgeting: A Critical Approach - Müge Yetkin Ataer (İstanbul İktisat Dergisi)
This study examines participatory budgeting practices by also covering benefits and critiques in the theoretical framework after providing definitions and general features. Subsequently, different applications from all over the world as well as the stage in which Turkey currently stands in terms of participatory budgeting have been put forward, with the context of direct-representative democracy being underlined alongside the problem of scope. Two different issues have been highlighted in line with the aim of this study. The first issue is related to the possibility that the process may evolve into political participation rather than individual participation in local administrations that are already chosen through representative democracy practices. The second issue is the risk of further harming those with the lowest incomes and marginalized/disadvantaged groups as a result of the efforts aimed at ensuring individual participation using the benefits of technological advancements. Particular policy recommendations have also been offered in the discussion on these issues.